Ispol'zovanie effekta polozhitel'nogo perenosa navyka v processe nachal'nogo obucheniya s predmetami v khudozhestvennoi gimnastike - Gorbachyova, J. S.; Stepanova, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to elaborate the methodics of initial learning in exercises with skipping rope and hoop, basing on the positive skills transference in the case of using the similiar motor actions. The data of the pedagogical experiment held by the author had proved the effectiveness of the elaborated methodsand means of initial learning in the above mentioned exercises.